Cathode active material, method for preparing the same, and lithium secondary battery comprising the same

By controlling the surface structure of secondary particles with plate-like primary particles, the material addresses structural and thermal stability issues in high-capacity layered lithium metal oxides, enhancing safety and performance.

JP2025013893AActive Publication Date: 2025-01-28CLEANSOLUTION CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024184300
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2018-09-12
Filing Date
2024-10-18
Publication Date
2025-01-28
Estimated Expiration
2039-09-16

Smart Images

  • Figure 2025013893000001_ABST
    Figure 2025013893000001_ABST
Patent Text Reader

Abstract

To provide a positive active material, a manufacturing method thereof, and a lithium secondary battery including the same, which are improved in thermal safety.SOLUTION: A positive active material is provided containing lithium metal oxide particles in a secondary particle form including primary particles, where the surface of the secondary particle includes planar primary particles with a narrow angle of 70 to 90° among angles between the c-axis of the primary particles and a straight line connecting a virtual point of a center of the primary particle and a center point of the secondary particle.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode active material, a method for producing the same, and a lithium secondary battery including the same. [Background technology]

[0002] Recently, the explosion of IT mobile devices and small power-driven devices (e-bikes, small EVs, etc.) This is driven by the sudden increase in demand and the need for electric vehicles with a driving range of over 400 km. The development of secondary batteries with high capacity and high energy density for driving is progressing actively worldwide. It is being considered.

[0003] In order to manufacture such a high-capacity battery, a high-capacity positive electrode active material must be used. stomach. The currently available layered positive electrode active material with the highest capacity is LiNiO 2 (275mAh / g), but the structure is prone to collapse during charging and discharging, and there is a problem with oxidized water. However, due to its low thermal stability, commercialization is currently difficult.

[0004] To solve this problem, it is necessary to add another stable transition metal to the unstable Ni site. (Co, Mn, etc.) must be replaced, and for this reason, Co and Mn are replaced. A ternary NCM system was developed. However, in the case of ternary NCM, the thermal stability decreases as the Ni content increases. do. Summary of the Invention [Problem to be solved by the invention]

[0005] Therefore, the present inventors have controlled the structure of the primary particles on the surface of the layered secondary particles to obtain a positive electrode surface. We propose a method to suppress the decomposition reaction of the electrolyte in the battery. The safety can be improved. [Means for solving the problem]

[0006] In one embodiment of the present invention, lithium metal oxide particles in the form of secondary particles including primary particles are The surface of the secondary particle is aligned with the c-axis of the primary particle; The narrowest angle between the line connecting the center point of the secondary particle and the point is 60 to 90 degrees. A positive electrode active material is provided that includes primary particles having a globular shape.

[0007] The surface of the secondary particle means the outermost part of the secondary particle which is formed by the primary particle.

[0008] FIG. 1 is a schematic diagram of a secondary particle according to one embodiment of the present invention.

[0009] As shown in Figure 1, in order to define the direction of the arrangement of the primary particles, the c-axis of the primary particles and the The narrowest angle between the imaginary point at the center of the secondary particle and the line connecting the center of the secondary particle is 60 to 90°. The primary particles having a plate-like shape are defined as having a plate-like shape. More specifically, the primary particles having a plate-like shape are defined as having a plate-like shape. Good too. Moreover, primary particles having an angle of 0° or more and less than 60° are defined as having an acicular shape. Specifically, it may be greater than 0° and less than 20°.

[0010] The plate-like particles on the surface of the secondary particles suppress side reactions with the electrolyte, and the positive electrode active material The thermal stability of the compound can be improved.

[0011] More specifically, the diameter of a circle having a radius of 50% of the radius of the secondary particle at the center point of the secondary particle is The area of ​​the plate-like primary particles is 20% or more of the total area of ​​the substrate. More specifically, it may be 30% by area or more.

[0012] Specifically, FIG. 2 is a SEM photograph of secondary particles according to one embodiment of the present invention.

[0013] As shown in Figure 2, a circle is set based on the center of the secondary particle, and then the area inside the circle is The area of ​​the platelet-shaped primary particles can be calculated. In this case, as shown in FIG. 2, the area occupied by the plate-shaped primary particles is 20% or more. In this case, as described above, the side reaction with the electrolyte can be effectively controlled. More preferably, it may be 50% by area or more, and more preferably, it may be 70% by area or more. The upper limit may be 100% of the total area of ​​the plate-like particles, but in practice, Some needle-shaped particles are present, and plate-shaped particles may account for up to 95% by area.

[0014] The area of ​​a circle that is 50% of the radius of the secondary particle at the center point of the secondary particle is 100%. %, the average length of the plate-like primary particles present within the above area is 750 nm to 1.2 It may be 5 μm.

[0015] The length of a plate-like primary particle means the length of the particle in the longest direction. When the thickness satisfies the above range, the desired battery characteristics can be ensured.

[0016] The inside of the secondary particle is defined by a c-axis of the primary particle and a virtual point at the center of the primary particle. and the center point of the secondary particle, the narrower angle is 0° or more and less than 60° More specifically, the primary particles may have a needle-like shape of 0 to 20°. The primary particles may be of the above formula (1).

[0017] More specifically, inside the secondary particles, needle-shaped particles are arranged toward the center of the secondary particles. It may be a radial structure.

[0018] The concentration gradient in the secondary particles where the nickel concentration decreases from the inside to the surface When the ion implantation step has a plurality of holes, such an internally directed structure can be formed.

[0019] In this case, the core of the secondary particle has a constant nickel concentration. This can be achieved by mixing the raw materials appropriately during the preparation of the precursor, which will be described later. can be tightly controlled.

[0020] More specifically, the nickel content in the metal in the secondary particles is 80 mol % or more. A high level that cannot be obtained with existing positive electrode active materials containing 50 mol % or less of nickel can be obtained. The nickel concentration can be increased for power characteristics.

[0021] In another embodiment of the present invention, the metal precursor is obtained by introducing an aqueous solution of metal salts into a coprecipitation reactor. and mixing the metal precursor and the lithium source material and then calcining the mixture to obtain a positive electrode active material. a step of introducing an aqueous metal salt solution into the coprecipitation reactor to obtain a metal precursor; The pH is in the range of 1 to 30% at the end of the reaction, based on the total reaction time of 100%. A method for producing a positive electrode active material by changing conditions is provided.

[0022] More specifically, a method of changing the pH at the end of the reaction in the stage of obtaining a precursor by coprecipitation reaction. In this case, the reaction completion time is 100% of the total reaction time. It can mean 1 to 30% from the last finish time.

[0023] More specifically, the reaction end point is the final end point of the entire reaction time of 100 hours. The concentration may be from 1 to 10% for a period of time or from 1 to 5% for a period of time.

[0024] This is because the shape of the plate-like primary particles on the surface of the positive electrode active material according to the embodiment of the present invention is The composition of the filter can be influenced and appropriately controlled to meet the desired specifications. Specifically, in the step of obtaining a metal precursor by introducing an aqueous metal salt solution into the coprecipitation reactor, The difference between the reaction start pH and reaction end pH may be 0.1 to 0.8.

[0025] More specifically, the reaction time is 1 to 30 hours relative to the total reaction time of 100 hours. %, the pH condition can be adjusted to be 0.1 to 0.8 higher. In this case, the plate-like particles present on the surfaces of the secondary particles can be formed uniformly.

[0026] More specifically, the rate of adjustment of the pH condition is 0.0016 to 0.0133 pH / min. More specifically, it may be 0.0066 to 0.0133 pH / min. Good too.

[0027] Such process conditions will be explained more specifically in the examples described below.

[0028] In another embodiment of the present invention, a positive electrode comprising the positive electrode active material according to the embodiment of the present invention described above is provided. a negative electrode including a negative electrode active material; and an electrolyte located between the positive and negative electrodes. We provide an uranium secondary battery.

[0029] The description of the positive electrode active material is the same as that of the embodiment of the present invention described above, and therefore will be omitted. do.

[0030] The positive electrode active material layer may include a binder and a conductive material.

[0031] The binder serves to adhere the positive electrode active material particles to each other well and to facilitate current collection. It acts as a good adhesive to the conductive material.

[0032] The conductive material is used to impart electrical conductivity to the electrodes. Any material that conducts electrons without undergoing chemical changes can be used in the pond. It is Noh.

[0033] The negative electrode includes a current collector and a negative electrode active material layer formed on the current collector. The material layer includes a negative electrode active material.

[0034] The negative electrode active material may be a material capable of reversibly inserting / extracting lithium ions, Metals, alloys of lithium metal, materials capable of doping and dedoping lithium, or transition metals Contains metal oxides.

[0035] The material capable of reversibly inserting / desorbing lithium ions is a carbon material. Any carbon-based negative electrode active material commonly used in lithium-ion secondary batteries can be used. Representative examples of such materials include crystalline carbon, amorphous carbon, or a combination of these. can be done.

[0036] The lithium metal alloy includes lithium and Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al and Sn An alloy with a metal selected from the group consisting of:

[0037] The material capable of doping and dedoping lithium includes Si, SiO x(0 <x< 2), Si-Y alloy (wherein Y is an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element, An element selected from the group consisting of elements, transition metals, rare earth elements, and combinations thereof. (Si is not included), Sn, SnO2, Sn-Y (Y is an alkali metal, alkali Earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations of these (An element selected from the group consisting of Sn and not Sn).

[0038] Examples of the transition metal oxide include vanadium oxide and lithium vanadium oxide. The negative electrode active material layer may further include a binder and may further include a conductive material. Good too.

[0039] The binder serves to adhere the negative electrode active material particles to each other well and to facilitate current collection. It acts as a good adhesive to the conductive material.

[0040] The conductive material is used to impart electrical conductivity to the electrodes. Any material that conducts electrons without undergoing chemical changes can be used in the pond. It is Noh.

[0041] The current collector may be made of copper foil, nickel foil, stainless steel foil, titanium foil, nickel carbide foil, or the like. Foam, copper foam, conductive metal coated polymer substrate, and Combinations selected from the group consisting of these may be used.

[0042] The negative electrode and the positive electrode are formed by mixing an active material, a conductive material, and a binder in a solvent to prepare an active material composition. The electrode is then produced by applying the composition to a current collector. Since this is well known in the art, detailed description will be omitted here. For example, N-methylpyrrolidone can be used, but is not limited to this. do not have.

[0043] The electrolyte includes a non-aqueous organic solvent and a lithium salt.

[0044] The non-aqueous organic solvent serves as a medium through which ions involved in the electrochemical reaction of the battery can move. Fulfill your quota.

[0045] The lithium salt dissolves in an organic solvent and acts as a source of lithium ions in the battery. It enables basic lithium secondary battery operation and regulates the transfer of lithium ions between the positive and negative electrodes. It is a substance that plays a role in promoting movement.

[0046] Depending on the type of lithium secondary battery, a separator may be present between the positive electrode and the negative electrode. Examples of such separators include polyethylene, polypropylene, polyvinylidene fluoride, etc. Polyethylene / polypropylene or multi-layered films of two or more layers of these can be used. 2-layer separator, polyethylene / polypropylene / polyethylene 3-layer separator, Mixed multi-layer films such as polypropylene / polyethylene / polypropylene triple layer separators Of course, it is possible to use

[0047] Lithium secondary batteries are classified into lithium-ion batteries depending on the type of separator and electrolyte used. They are classified into lithium-ion polymer batteries and lithium polymer batteries, and are divided into They are classified into cylindrical, square, coin, pouch, etc., and are divided into bulk and thin film types depending on the size. The structure and manufacturing method of these batteries are widely known in the art. , detailed explanation will be omitted. Effect of the Invention

[0048] In the positive electrode active material according to one embodiment of the present invention, the plate-shaped surface with low reactivity is in contact with the electrolyte, This makes it possible to suppress the decomposition reaction of the electrolyte on the surface of the positive electrode. The reduction in side reactions of the electrolyte improves the thermal stability of the positive electrode active material. More specifically, during DSC analysis, the peak temperature increases and the total heat release decreases, resulting in thermal safety. It is possible to provide a positive electrode active material having improved properties. [Brief description of the drawings]

[0049] [Figure 1] FIG. 2 is a schematic diagram of a secondary particle according to one embodiment of the present invention. [Diagram 2] 2 shows the shape of primary particles present on the surface of the positive electrode active material of Example 1. [Diagram 3] 1 shows the shape of primary particles present on the surface of the positive electrode active material of Example 3. [Figure 4] 2 shows the shape of primary particles present on the surface of the positive electrode active material of Comparative Example 1. [Diagram 5] 1 shows the cross-sectional shape of a positive electrode active material of Example 1. [Figure 6] 1 shows the cross-sectional shape of a positive electrode active material of Example 3. [Figure 7] 3 is a cross-sectional shape of a positive electrode active material of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0050] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail by way of example only. However, the present invention is not limited thereto, and the present invention is limited only by the scope of the claims described below. is defined.

[0051] (Example 1) Preparation of positive electrode active material containing 88 mol% Ni 1) Preparation of metal salt solutions First, NiSO4·6H2O is used as the nickel source material, and C is used as the cobalt source material. oSO4·7H2O, MnSO4·H2O is used as manganese raw material, and Ni, C Two aqueous solutions of metal salts with different concentrations of o and Mn were prepared. The first metal salt aqueous solution for forming the core was dissolved in distilled water (Ni 0.98 Co 0.01 Mn 0.01 The raw materials were mixed so as to satisfy the stoichiometric molar ratio of )(OH)2. Independently, the second metal salt aqueous solution for the shell formation was dissolved in distilled water (Ni 0. 64 Co 0.23 Mn 0.13 )(OH)2 so as to satisfy the stoichiometric molar ratio of each of the above ingredients. The materials were mixed.

[0052] 2) Co-precipitation process A coprecipitation reactor was prepared in which two metal salt aqueous solution supply tanks were connected in series. The first metal salt aqueous solution and the second metal salt aqueous solution were charged into a metal salt aqueous solution supply tank. Distilled water was added to the coprecipitation reactor, and the reactor temperature was kept constant while stirring. In addition, NH4(OH) is used as a chelating agent, and NaOH solution is used as a pH adjuster. did. At this time, the initial pH in the reactor during the reaction was set to 11.2.

[0053] In this way, the pH is kept constant and the chelating agent is supplied to the reactor. The supply time and amount of each metal salt solution were adjusted from two metal salt aqueous solution supply tanks. Specifically, the first metal salt aqueous solution was added at a rate of 0.4 L / hour while the precipitate was The coprecipitation reaction was carried out until the diameter reached approximately 11.1 μm. At this time, the flow rate was adjusted to reduce the reaction of the solution. The average residence time in the reactor is about 10 hours, and after the reaction reaches a steady state, The reaction is allowed to stand for a period of time to obtain a denser coprecipitate. did.

[0054] Next, while changing the mixing ratio of the first metal salt aqueous solution and the second metal salt aqueous solution, The total feed solution was added at 0.4 liters / hour, and the feed rate of the first metal salt aqueous solution was 0. The feed rate of the second metal salt aqueous solution was gradually reduced to 0.35 L / h. The flow rate was gradually increased at 100 ml / hour. At this time, the average residence time of the solution in the reactor was adjusted by adjusting the flow rate. The time should be within 20 hours, and the precipitates were mixed together until their diameters reached 16.0 μm. A precipitation reaction was carried out. At this time, the pH was adjusted to a high level of 12.0 one hour before the end of the reaction. The pH was 0.0133 pH / min.

[0055] 3) Post-processing The precipitate obtained by the series of coprecipitation steps was filtered, washed with water, and then heated at 100°C. After drying in an oven for 24 hours, the composition of the whole particle was (Ni 0.88 Co 0. 095 Mn 0.025 )(OH)2, and the average particle size is 16.0 μm. An active material precursor was prepared.

[0056] 4) Firing process There is a core-shell concentration gradient, and Ni 0.88 Co 0.095 Mn 0.025 (OH)2 A precursor with the composition of and ZrO2 (Aldrich, 4N, Zr concentration 3,400ppm m standard), Al(OH)3 (Aldrich, 4N, Al concentration standard 140 ppm) Then, LiOH·H2O (Samchun Chemical, ery grade) in a molar ratio of 1:1.05 and then heated in a furnace. The mixture was charged into a furnace and fired under a flow of oxygen.

[0057] Thereafter, the mixture was naturally cooled, and then crushed and classified to produce a positive electrode active material.

[0058] (Example 2) Preparation of positive electrode active material containing 88 mol% Ni When preparing the raw material, (Ni 0.88 Co 0.095 Mn 0.025 )(OH)2 The molar ratio was adjusted to meet the reaction start pH during the coprecipitation process to 11.2. The pH was adjusted to 11.8 one hour before the end of the reaction. A positive electrode active material was produced in the same manner as in Example 1, except that the speed was adjusted to 0.01 pH / min. did.

[0059] (Example 3) Preparation of positive electrode active material containing 88 mol% Ni In the coprecipitation process, the reaction start pH was adjusted to 11.2 during the reaction, and the pH was adjusted to 11.2 one hour before the end of the reaction. H was adjusted to the range of 11.6, and the pH adjustment rate was adjusted to 0.0066 pH / min. A positive electrode active material was produced in the same manner as in Example 2, except for the above-mentioned adjustment.

[0060] (Example 4) Preparation of positive electrode active material containing 88 mol% Ni In the coprecipitation process, the reaction start pH was adjusted to 11.2 during the reaction, and the pH was adjusted to 11.2 one hour before the end of the reaction. The pH was adjusted to 11.4 and the pH adjustment rate was adjusted to 0.0033 pH / min. A positive electrode active material was produced in the same manner as in Example 2, except for the above-mentioned adjustment.

[0061] (Comparative Example 1) Preparation of positive electrode active material containing 88 mol% Ni The same procedure as in Example 2 was repeated except that the pH was maintained at 11.0 during the coprecipitation step. A positive electrode active material was produced in the same manner as described above.

[0062] [Table 1]

[0063] (Experimental Example 1) Shape analysis of the surface of the positive electrode active material (SEM) The positive electrode active materials of Example 1, Example 3, and Comparative Example 1 were analyzed by SEM. The shape of the primary particles present on the surface was observed.

[0064] FIG. 2 shows the shape of primary particles present on the surface of the positive electrode active material of Example 1, and one of the primary particles has a plate-like shape. It was confirmed that the secondary particles uniformly surrounded the entire surface of the positive electrode active material. The surface (c-axis surface) is a surface where the Li intercalation / deintercalation reaction does not occur, so the electric potential on the surface of the positive electrode It is expected that the decomposition reaction of the solution was suppressed.

[0065] FIG. 3 shows the shape of primary particles present on the surface of the positive electrode active material of Example 3. The secondary particles and acicular particles are present mixed on the surface of the positive electrode active material.

[0066] FIG. 4 shows the shape of primary particles present on the surface of the positive electrode active material of Comparative Example 1, and shows the shape of the primary particles. The secondary particles are uniformly distributed. This is the same shape as that usually observed when manufacturing a positive electrode active material. is similar to

[0067] (Experimental Example 2) Shape analysis of cross section of positive electrode active material (TEM) The cross sections of the positive electrode active materials of Example 1, Example 3, and Comparative Example 1 were cut using FIB and analyzed by TEM. The shape distribution of primary particles in the cross section of the positive electrode material was observed using an analyzer.

[0068] FIG. 5 shows the cross-sectional shape of the positive electrode active material of Example 1, and FIG. 6 shows the cross-sectional shape of the positive electrode active material of Example 3. 7 shows the cross-sectional shape of the positive electrode active material of Comparative Example 1. The arrangement of the primary particles inside the positive electrode active material was acicular in all of Examples 1, 3, and Comparative Example 1. Numerous needle-shaped particles are observed, showing a radial morphology arranged toward the center of the secondary particles.

[0069] However, in the case of the arrangement of the primary particles on the surface of the positive electrode active material, Comparative Example 1 was similar to the interior and had needle-like structure. In the case of Example 3, the primary particles exhibited a plate-like morphology and the primary particles exhibited a needle-like morphology. It can be confirmed that primary particles are mixed with the crystalline particles. It can be seen that the positive electrode active material of Example 1 contains more plate-shaped particles.

[0070] In the positive electrode active materials of Examples 1 to 4 and Comparative Example 1, primary particles having a plate-like shape were formed on the surface. We investigated how much of the surface area the sintered matter occupies. This was confirmed by the following method.

[0071] As shown in FIG. 2, the SEM photograph of the secondary particle is used as a reference, and the secondary particle at the center The area occupied by plate-shaped particles relative to the area of ​​a circle with a radius of 50% of the primary particle (100% of the total area) The product was calculated.

[0072] [Table 2]

[0073] (Experimental Example 3) Differential Scanning Calorimetry in the Charged State ng Calorimetry, DSC) The positive electrode active materials of Examples 1 to 4 and Comparative Example 1 were used in the manufacture of coin cells and the charging of the coin cells. The battery was disassembled and the thermal stability of the positive electrode active material was analyzed by DSC.

[0074] The slurry for the electrodes is composed of the following: positive electrode, conductive material (denka black), binder (PVDF , KF1100) = 92.5:3.5:4 wt%, so that the solid content is about 30%. Add NMP (N-Methyl-2-pyrrolidone) to reduce the viscosity of the slurry. Adjusted. The prepared slurry was coated onto an Al foil with a thickness of 15 μm by a doctor blade method. After that, it was dried and rolled. The electrode loading is 14.6mg / cm 2 and the rolling density is 3.1 g / cm 3 in The electrolyte was 1M LiPF6in ethylene carbonate:dimethyl carbonate. : Ethyl methyl carbonate = 3:4:3 (vol%), polypropylene separator A coin cell was manufactured using the lithium anode (200um, Honzo metal). Charging conditions are CC / CV 2.5~4.25V, 1 / 20C cut-off. there were. After that, the coin cell was disassembled in a dry room, and 10 mg of the positive electrode active material was extracted and analyzed by DSC. An analysis was conducted.

[0075] DSC analysis was performed at 25°C to 400°C at 5°C / min. After analyzing the set temperature, the peak temperature at which the heat generation is maximum, and the total heat generation, the results are shown in the table below. I have summarized it in 3.

[0076] (Experimental Example 4) Electrochemical Characterization The positive electrode active materials of Examples 1 to 4 and Comparative Example 1 were mixed in a 2032 coin-shaped After manufacturing the half-cell, it was aged at room temperature (25°C) for 10 hours and then subjected to charge / discharge tests. They went on strike.

[0077] The capacity evaluation was based on a standard capacity of 215mAh / g, and the charge / discharge conditions were CC / CV2.5~4.2. 5V, 1 / 20C cut-off applied. Initial capacity is 0.2C charge / 0.2C discharge. It went under the conditions.

[0078] [Table 3]

[0079] From Table 3 above, it can be seen that the peak temperature of the active material of the embodiment increases, the total heat generation decreases, and the thermal stability is improved. It is clear that the integrity has improved.

[0080] [Table 4]

[0081] As can be seen from Table 4, the positive electrode active material according to the embodiment of the present application has the thermal stability as shown in Table 3. Although the charge / discharge capacity and efficiency are significantly improved, the charge / discharge capacity and efficiency are comparable to those of Comparative Example 1. It becomes clear that...

[0082] The present invention is not limited to the above-described embodiments and may be manufactured in a variety of different forms. It is possible to understand the technical concept of the present invention by a person having ordinary skill in the art to which the present invention pertains. It is understood that the present invention may be embodied in other specific forms without changing the concept or essential characteristics. Therefore, the above-described embodiment is illustrative in all respects and is not restrictive. It must be understood that there is no.

Claims

1. Lithium metal oxide particles in the form of secondary particles including primary particles, The surface of the secondary particle is a c-axis of the primary particle; A plate-like shape in which the narrowest angle between the center point of the secondary particle and the line connecting the center point of the secondary particle is 60 to 90 degrees. The positive electrode active material includes a secondary particle.

2. The area of ​​a circle at the center point of the secondary particle that is 50% of the radius of the secondary particle is 100 For area %, 2. The positive electrode according to claim 1, wherein the area occupied by the plate-like primary particles is 20% by area or more. active material.

3. The area of ​​a circle at the center point of the secondary particle that is 50% of the radius of the secondary particle is 100 For area %, The average length of the plate-like primary particles present within the area is 750 nm to 1.25 μm. The positive electrode active material according to claim 2 .

4. The inside of the secondary particle is a c-axis of the primary particle; and a virtual point of the center of the primary particle and a virtual point of the center of the secondary particle. The narrowest angle between the straight line and the needle-shaped primary particles is 0° or more and less than 70°. The positive electrode active material according to claim 1 .

5. The content of nickel in the metal in the secondary particles is 80 mol % or more.

2. The positive electrode active material according to claim 1.

6. Introduction of an aqueous metal salt solution into a coprecipitation reactor to obtain a metal precursor; and mixing the metal precursor and the lithium source material, and then calcining the mixture to obtain a positive electrode active material; Including, In the step of obtaining a metal precursor by introducing an aqueous metal salt solution into the coprecipitation reactor, The pH condition is adjusted within the range of 1 to 30% at the end of the reaction, based on the total reaction time of 100 hours. A method for producing a positive electrode active material that changes the

7. In the step of obtaining a metal precursor by introducing an aqueous metal salt solution into the coprecipitation reactor, the reaction start p The method for producing a positive electrode active material according to claim 6, wherein the difference between H and the reaction end pH is 0.1 to 0.

8. method.

8. In the range of 1 to 30 hours at the end of the reaction relative to the total reaction time of 100 hours. The method for producing a positive electrode active material according to claim 6, wherein the pH condition is adjusted to be 0.1 to 0.8 higher.

9. The rate of adjustment of the pH condition is 0.0016 to 0.0133 pH / min.

9. A method for producing a positive electrode active material according to claim 8.

10. A positive electrode comprising the positive electrode active material according to any one of claims 1 to 5; a negative electrode comprising a negative electrode active material; and an electrolyte located between the positive electrode and the negative electrode.

Citation Information

Patent Citations

  • Positive electrode active material precursor for secondary battery and positive electrode active material for secondary battery prepared by using the same

    KR1020180063862A

  • Nickel manganese composite hydroxide, production method for nickel manganese composite hydroxide, positive electrode active material for non-aqueous electrolyte secondary battery, production method for positive electrode active material for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery

    WO2018021557A1